2021
DOI: 10.3390/w13162187
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Drinking Groundwater As Phytofiltration by the Hyperaccumulating Fern Pteris vittata

Abstract: The reuse of Pteris vittata plants for multiple phytofiltration cycles is a main issue to allow an efficient phytoremediation of arsenic (As)-contaminated groundwater. Here, we assessed the capacity of phytofiltration of P. vittata plants grown for two cycles on naturally As-contaminated drinking water (collected in Central Italy), spaced by a growth cycle on non-contaminated water (N cycle). P. vittata young plants, with extensive frond and root development, were suspended individually in 15 L of water with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Thus, the ferns were moved to net pots filled with expanded clay and placed in 15L tanks of tap water for hydroponic culture. Each tank hosted 12 ferns, and after 4–5 months, the roots occupied most of the space in the tank; thus, the roots were cut and harvested [ 18 ]. The waste roots were pretreated before the adsorption tests, following the procedure reported in the work of Mazzeo et al [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the ferns were moved to net pots filled with expanded clay and placed in 15L tanks of tap water for hydroponic culture. Each tank hosted 12 ferns, and after 4–5 months, the roots occupied most of the space in the tank; thus, the roots were cut and harvested [ 18 ]. The waste roots were pretreated before the adsorption tests, following the procedure reported in the work of Mazzeo et al [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have documented the ability of PV to remove large amounts of arsenic (As) (up to 23.000 mg/kg) from soil [ 15 ] and directly from the water in hydroponic culture systems [ 16 , 17 ]. Multiple phytoremediation cycles were also successfully conducted [ 18 ] showing that PV does not release any of the previously accumulated As.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation and growth of ferns were performed in the greenhouse under controlled conditions as previously described [19,25]. Six-month-old ferns with 7-8 fronds and about 30 cm tall were transferred in pots containing soils naturally rich in As, with two different As concentrations: Soil 1 (S1) and Soil 2 (S2), with average As concentrations of 58 mg/kg and 750 mg/kg, respectively (Figure 1).…”
Section: Plant Growth and Pinna Powder Preparationmentioning
confidence: 99%
“…Measurement of As in the biomass of plants evaluating their bioaccumulation requires expensive, invasive and timeconsuming laboratory chemical methods [9]. We have previously shown that young plants of Pteris vittata when transferred to naturally As-contaminated groundwater are able to remove up to 98% of As in 60 days [10]. Here a comparative evaluation was performed on Pteris vittata leaves collected from plants grown on As contaminated and not contaminated water adopting reflectance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%